Pengaruh Self Confidence Terhadap Psikomotor Atlet Club Bola Voli Pawit Mulya - Sumarko, Mayang Anjanika; Kusmiyati; Sugiyono (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of self-confidence on the psychomotor abilities of Pawit Mulya Volleyball Club athletes. The research was motivated by the continued discovery of athletes who show doubts in performing basic volleyball techniques, which is suspected to be related to low levels of self-confidence. This study used a quantitative approach with a correlational design. The research sample consisted of 14 athletes determined using a saturated sampling technique. Data were collected through self-confidence questionnaires, psychomotor ability observations, interviews, and documentation. Data analysis was carried out using normality tests, simple linear regression analysis, coefficient of determination tests, and t-tests with the help of IBM SPSS Statistics 16.0. The results showed that self-confidence had a significant effect on the psychomotor abilities of athletes with a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) value of 0.984 indicates that self-confidence contributed 98.4% to the variation in athletes' psychomotor abilities, while the rest was influenced by other factors outside the study. Thus, the higher the level of self-confidence an athlete has, the better the psychomotor abilities they demonstrate. These findings indicate that developing psychological aspects, especially self-confidence, needs to be an important part of volleyball athlete development programs.